The blue raven - Van Camp, Richard 1971- (Pearson, 2015)
Benji and Trevor form an unlikely friendship when Benji's bike, which used to belong to his father, is stolen
Includes discussion questions
Keywords: Geschiedene Eltern; Freundschaft; Fahrraddiebstahl; Indianer; Kanada; Indigenous peoples / Canada / Juvenile fiction; Children of separated parents / Juvenile fiction; Bicycle theft / Juvenile fiction; Friendship / Juvenile fiction; Graphic novels / Canada; Bicycle theft; Children of separated parents; Friendship; Graphic novels; Indigenous peoples; Canada; Fiction; Juvenile works; Comic